Artificial Intelligence, School Administration and Teachers’ Job Performance in Public Post-Basic Education and Career Development (PBECD) in FCT, Nigeria (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This study invested the impact of AI on school administration and teachers’ job performance in Public Post-Basic Education and Career Development (PBECD) in FCT, Nigeria. This study adopted survey research design and correctional method. The target population for this study consisted of all Principals and all teachers in Public Post-Basic Education and Career Development (PBECD) in FCT, Nigeria. The sample size consisted of 50 Principals and 150 teachers giving the total as 200 which were drawn from some selected the sample schools. The sample size was randomly selected. The instrument for this study was questionnaire titled ‘AI, School administration and Teachers’ job performance Questionnaire’ (ASTQ). The questionnaire comprised Agree (SA) =4, Agree (A) =3, Disagree (D) =2 and strongly Disagree (SD) =1. The split-half reliability coefficient then is determined by correlating the scores. Based on the standard indices for reliability coefficient obtained for the instrument (0.94 and 0.94) are an indication of high reliability, pointing to the suitability of the instrument. The data collected were quantitatively analysed using tables, frequency distribution, percentage and Person Product Moment Correlation Coefficient (PPMCC). The study revealed that AI has significant relationship with school administration in Public Post-Basic Education and Career Development (PBECD), FCT, Nigeria. The study also disclosed that AI has significant relationship with teachers’ job performance in Public Post-Basic Education and Career Development (PBECD), FCT, Nigeria. Based on this finding, the paper recommends that government should increase funding of Public Post-Basic Education and Career Development (PBECD) in FCT for the development of artificial intelligence in all Public Post-Basic Education and Career Development (PBECD) in FCT. Government should organize capacity building programme for school administrators and teachers to improve their digital capacity and digital knowledge.